2008
DOI: 10.1017/s1751731107001073
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of adult ewes during early and mid-pregnancy. 2. Effects of supplementation with selenised yeast on ewe reproduction and offspring performance to weaning

Abstract: The objective of this study was to determine the effects of selenium (Se) supplementation of mature ewes in the period from day 214 to day 90 post mating on Se status, productivity and viability of ewes and their offspring. Multiparous crossbred ewes (n 5 82) were randomly assigned to receive a standard dried grass-based diet (control) or dried grass diet supplemented with 1 g of selenised yeast (Selplex R ), providing 0.5 mg Se per ewe per day. After day 90 post mating, all ewes were offered grassbased diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
(34 reference statements)
3
15
0
Order By: Relevance
“…Within each combination of EP and MP treatments half of the ewes received a selenium supplement (0.5 mg Se/ewe per day), offered from day 214 to day 90 of pregnancy (year 1 5 Selplex R ; Alltech, Belfast, Northern Ireland, UK; year 2 5 Retosel Premix 4.5% R ; Trouw Nutrition, Belfast, Northern Ireland, UK) as described in Muñ oz et al (2008b). During EP and MP, diets were supplemented daily with 25 g of barley, as a vehicle for the intake of selenium and 25 g of straw as a source of fibre.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Within each combination of EP and MP treatments half of the ewes received a selenium supplement (0.5 mg Se/ewe per day), offered from day 214 to day 90 of pregnancy (year 1 5 Selplex R ; Alltech, Belfast, Northern Ireland, UK; year 2 5 Retosel Premix 4.5% R ; Trouw Nutrition, Belfast, Northern Ireland, UK) as described in Muñ oz et al (2008b). During EP and MP, diets were supplemented daily with 25 g of barley, as a vehicle for the intake of selenium and 25 g of straw as a source of fibre.…”
Section: Experimental Designmentioning
confidence: 99%
“…Ewe and lamb behaviours were recorded continuously for the first 30 min after the birth of each lamb, using handheld data recorders and the observer software system for behaviour research (Noldus Information Technology, Wageningen, The Netherlands). The definition of maternal behaviours was based on Dwyer and Lawrence (1998), while neonatal lamb behaviours were based on Dwyer et al (1996), and have been described previously (Muñ oz et al, 2008b).…”
Section: Measurementsmentioning
confidence: 99%
“…Although symptoms of clinical Se deficiency are uncommon, Se inadequacy is widely reported throughout the United Kingdom and Ireland (Wang et al, 1987;Mee et al, 1994). Studies in sheep have reported increased live weight gain in lambs following Se supplementation both directly (Blaxter, 1963) and indirectly via their dams (Muñ oz et al, 2008 and. Feeding high PUFA diets can lead to increased oxidative stress in lambs; however, there is some evidence that feeding supranutritional levels of vitamin E help protect against lipid peroxidation, resulting in increased PUFA levels in the meat (Demirel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Foetuses from Se-supplemented ewes had greater body weights. Munoz et al (2006) fed an additional 500 mg organically bound Se daily from 14 days before mating to day 90 of pregnancy. Initial mean GPx activities ( ,33 U per ml red blood cells) were in the low to marginal range.…”
mentioning
confidence: 99%